DEVELOPEMENT OF NEGOTIATING COMPETENCIES FOR BUSINESS MANAGEMENT STUDENTS - Peleckis, Kęstutis; Peleckienė, Valentina; Okunevičiūtė Neverauskienė, Laima; K. Peleckis, Kęstutis (IJRDO - Journal of Social Science and Humanities Research, 2017)
The paper discusses problems related to negotiation skills of the students of business administration and deals with the issues of structure and content. The article discloses and describes the structural elements of negotiation skills acquired by business managers: personal characteristics, values, attitudes, background, skills, abilities, emotional intelligence and charisma. The article also focuses on individual work with students, the principles of student centred learning and assumptions about developing managerial and negotiation skills. The paper looks at the structural elements of negotiation skills and emphasizes its content can be developed with reference to a planned, systematic and holistic approach. For this purpose, the areas and fields where the bargaining skills of business management students should be developed have been highlighted. In order to more effectively develop negotiation skills of business management students, an argument for the necessity of shifting from teaching supported by knowledge based education (knowledge based approach) to the learning paradigm where education is based on competences (competency based approach) has been put forward: assessing learning as a process involving student thinking, perception, feelings, emotions, behavioral processes and their changes during the process of training with an emphasis on accumulated student experience significant to the meaningful educational process thus revealing the growth of his/her skills (to observe, experience, understand, assimilate, learn) in real or simulated learning activities.